Rekomendasi Pemilihan Paket Personal Computer Menggunakan Metode AHP-TOPSIS - Bhima Arya Tristya Haryu Niswara; Rekyan Regarsari Mardhi Putri; Nurul Hidayat (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
In this era, Personal Computer enter phase of the rapid development. Formerly PC often found in large companies, but it can be found in many private houses nowadays. The PC becomes a necessity in everyday activities from office work, college tasks, even for daily communication. Along with the many enthusiasts to have a personal computer, theres so many builder who don't know what is needed to build a PC. In addition, the many types of components offered to make the builder more confused in choosing the components, as well as with limited budget. From the problems mentioned there are solutions by using Decission Support System that can provide the best alternative to the computer maker in decision making, DSS is software that provides output in the form of alternative solutions. Required method in implementing DSS, in this research using AHP and TOPSIS combined method. The AHP method has a priority comparison of each critera, and TOPSIS has the advantage of providing preferential results in the form of the most ideal solution in accordance with the desired criteria, so the user gets recommendations according to his wishes. The result of implementation of recommendation of personal computer build using AHP-TOPSIS method got 74% accuracy.